2018
DOI: 10.1007/jhep10(2018)204
|View full text |Cite
|
Sign up to set email alerts
|

Calogero-Sutherland approach to defect blocks

Abstract: Extended objects such as line or surface operators, interfaces or boundaries play an important role in conformal field theory. Here we propose a systematic approach to the relevant conformal blocks which are argued to coincide with the wave functions of an integrable multi-particle Calogero-Sutherland problem. This generalizes a recent observation in [1] and makes extensive mathematical results from the modern theory of multi-variable hypergeometric functions available for studies of conformal defects. Applica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 76 publications
4
88
0
Order By: Relevance
“…The connection uncovered in [17] implies that conformal blocks are certain multivariable hypergeometric functions with properties that follow from integrability of the quantum mechanical system and are very similar to those of ordinary hypergeometrics in one variable. Later, it was shown that the relation between conformal blocks and Calogero-Sutherland models is universal in that it applies to spinning and defect blocks etc, see [19][20][21].…”
Section: Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The connection uncovered in [17] implies that conformal blocks are certain multivariable hypergeometric functions with properties that follow from integrability of the quantum mechanical system and are very similar to those of ordinary hypergeometrics in one variable. Later, it was shown that the relation between conformal blocks and Calogero-Sutherland models is universal in that it applies to spinning and defect blocks etc, see [19][20][21].…”
Section: Contentsmentioning
confidence: 99%
“…Such a configuration admits two channels, the defect and the bulk channel [21,[61][62][63]. While defect channel blocks split into simple products of hypergeometric functions in one variable [61], the construction for bulk channel blocks with scalar external fields was only completed recently in [21], see also [62] for earlier results. An extension to bulk channel blocks for spinning operators was initiated recently in [63].…”
Section: Applications To 4-dimensional N = 1 Theoriesmentioning
confidence: 99%
“…New connections to mathematics and new applications are still coming to light in the current literature, see e.g. [6,7,22,24,46,53].The richness of these models is also due to their many generalizations and deformations. These are associated with different interaction potentials (from rational to elliptic), root systems and extensions with internal degrees of freedom.…”
mentioning
confidence: 99%
“…New connections to mathematics and new applications are still coming to light in the current literature, see e.g. [6,7,22,24,46,53].…”
mentioning
confidence: 99%
“…More recently, Lorentzian CFT's have attracted renewed interest in light of the novel development in analytic bootstrap in lightcone [20][21][22], the Regge limits of correlation functions [23][24][25][26][27], and the remarkable applications in deriving averaged null energy condition in flat space [28,29] and the Lorentzian inversion formula [30,31]. Conformal blocks play a vital role also there as a probe of causal relationships between operators in Minkowski space, whose structures have been deeply tied to a class of quantum integrable systems in the past few years [32][33][34].…”
Section: Contentsmentioning
confidence: 99%